Hybrid Work Models And People Analytics A Critical Review On Work-Life Balance, Productivity, And Predictive Human Capital Strategies (International Journal of Environmental Sciences, 2025)
Hybrid work has led to a major shift in organizations, altering the way, place and time employees handle their job duties. With these models, people can work flexibly and independently which helps them fit well into both their personal and work lives. But they also create difficulties such as feeling tired from using technology, less team unity and blending the work and home life. As a result, people analytics is now an important tool for tracking workforce changes, helping with key decisions and improving the organization’s ability to keep going through difficult times. This article looks at the relationship between hybrid work and using advanced analytics in managing employees. It uses both theories and research findings to study the effects of hybrid systems on both individual happiness and organizational performance. It points out that digital ecosystems, ethical data collection, predictive modeling and leadership changes all play a part in making hybrid work successful. It has been found that when hybrid work is supported with the right tools and policies, people tend to be more satisfied, involved and productive. The use of predictive workforce analytics helps more by finding new trends in employee actions, boosting achievements and matching each person’s experience with the organization’s goals. Even so, the review points out important issues, for example, ensuring policies are fair, using scientifically sound methods to assess employee experience and ensuring algorithms are used ethically. To conclude, the paper provides a useful model to guide those in charge of creating inclusive, data-driven and forward-thinking hybrid workplaces. It also identifies important research topics that centre on inclusivity, follow-up studies and open management of people analytics systems.